Application of Blade-Tip Sensors to Blade-Vibration Monitoring in Gas Turbines - Szczepanik, Ryszard; Przysowa, Radosław; Spychała, Jarosław; Rokicki, Edward; Kaźmierczak, Krzysztof; Majewski, Paweł (IntechOpen, 2012)
None